(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2023)
The leaves of roselle (Hibiscus sabdariffa L.) are usually used in food and traditional medicine. It also has been recognized as a source of natural antioxidants. Antioxidants are known as molecules that prevent the oxidation process caused by free radical compounds that can harm the human body. Thus, this study aims to characterize the chemical constituents found in ethanolic extracts of red roselle (RR) and white roselle (WR) leaves and determine their antioxidant activity. The phytochemical screening indicated that RR leaf extract contained phenols, tannins, saponins and steroids, while WR leaf extracts consisted of phenols, tannins and reducing sugars. The total phenolic content in RR and WR leaf extracts was 42.07 ± 0.48 mg GAE/g dry weight of leaf and 38.59 ± 1.75 mg GAE/g dry weight of leaf, respectively, while the DPPH radical scavenging activity was 85.65 ± 0.33 % and 83.49 ± 0.13 % at a concentration of 1 mg/ml for RR and WR extracts. Total phenolic content and antioxidant activity showed that RR leaf extract was significantly higher than WR leaf extract. Thin layer chromatography (TLC) separation revealed a few prominent spots in both crude extracts, which were polar in nature. The TLC results can be used as preliminary data to further investigate the compounds. Characterization of the isolated crude compounds in the extracts was done using Fourier-transform infrared (FTIR). The infrared spectrum exhibited the presence of hydroxyl group, carboxylic acids, alkanes, the presence of esters (-C=O) and the involvement of aromatic structure of the compound. The study demonstrated the ethanolic extract of two varieties of roselle leaf contains phytochemical constituents that could contribute to the antioxidant activity. The findings of this study will contribute to the development of herbal teas or food supplements to maintain good health. The data from this study will also provide valuable information for future research on the fractionation and purification of potential antioxidant compounds found in the extract.